Impact of Conversion from Laparoscopy to Open Surgery in Patients with Right Colon Cancer. Issue 2 (February 2019) - Petrucciani, Niccolò; Memeo, Riccardo; Genova, Pietro; Roy, Bertrand Le; Courtot, Lise; Voron, Thibault; Aprodu, Razvan; Tabchouri, Nicolas; Saleh, Nour Bou; Berger, Anne; Ouaïssi, Mehdi; Pezet, Denis; et al.
Conversion to open surgery is reported in up to 20 per cent of laparoscopic colectomies for cancer. This study aims to compare postoperative outcomes and survival between converted and successful laparoscopic right colectomy for cancer. Records of patients who underwent laparoscopic right colectomy for cancer between 2005 and 2015 were retrieved from the CLermontFerrand Ircad Mondor Hopital European Tours (CLIMHET) database. Perioperative, postoperative, and survival outcomes were evaluated. Multivariate analysis was performed to identify predictive factors for conversion. Overall, 445 patients underwent a successfully completed laparoscopic right colectomy and 28 (5.9%) were converted to open surgery. A higher rate of minor complications was found in the conversion group, whereas patient recovery outcomes were similar. Previous open and laparoscopic surgeries were significant predictors of conversion. No significant difference was found in overall and disease-free survival rates between converted and nonconverted procedures. In the setting of laparoscopic right colectomy for cancer, the conversion rate is low and does not have an impact on patient survival. Conversion is associated with higher rates of minor postoperative complications but recovery and survival outcomes are comparable with successful laparoscopic colectomies. The present results support the use of laparoscopy for right colon resection even in patients at risk of conversion.